The The Perception Of Hindu Community In Mataram Toward Changing On Customary Marriage Behavior - Ida Ayu Nyoman Widia Laksmi (Jayapangus Press, 2021)
This research is motivated by a change in the traditional marriage system in the Hindu community in the city of Mataram. The purpose of this study was to examine the perception of the Hindu community in the city of Mataram on changes in customary marriage behavior. Methods of this research is designed in a qualitative descriptive type with a case study model. Data were collected by observation, interview, and documentation. The collected data were analyzed using qualitative analysis techniques through data grouping, data reduction, and data interpretation. The summary of the results of this study that the Hindu community's perception of changes in customary marriage behavior in the city of Mataram could be categorized into two, namely the group that agreed and the other group did not agree. The category agreed with the reasons (1) polite and more honorable; (2) fostering a more harmonious relationship between the two parties; (3) social status and wangsa (line of descent); (4) consensual; and (5) a simpler process. Groups that disagree are categorized into three, namely (1) cultural traditions and customs; (2) ethics and courtesy; and (3) the wangsa (line of descent). The perception of the Hindu community in the city of Mataram on the mepadik and selarian marriage system in terms of time, energy and cost. Based on the results of the study it was found that the public perception of the mepadik marriage system in terms of time, then the time used was less when compared to the selarian system. The implications of changing marital behavior in terms of energy, then the energy needed in the marriage process that uses the mepadik system will use less energy when compared to the selarian system. In terms of financing, the occurrence of cost efficiency in the mepadik marriage system.